2019 2nd West Asian Colloquium on Optical Wireless Communications (WACOWC) 2019
DOI: 10.1109/wacowc.2019.8770202
|View full text |Cite
|
Sign up to set email alerts
|

On Limitations of Using Silicon Photo-Multipliers for Underwater Wireless Optical Communications

Abstract: This paper considers the use of Silicon photomultipliers in underwater wireless optical communication systems. We study the limitations arising from the limited bandwidth of these components as well as the solar background noise in relatively shallow waters. In particular, we show the interest of frequency-domain equalization in increasing the link data rate using on-off-keying and pulse-position modulation. Also, for a worst-case scenario, we determine the operation depth (with respect to the receiver) beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although we neglected the effect of background noise, it can severely affect the Rx performance due to the high sensitivity of SiPMs. In a recent study [39], the impact of solar background noise on the link performance was investigated for a worst-case scenario, i.e., sun at the zenith and the Rx plan directed towards the sea surface, this way, capturing the maximum solar irradiation [30]. It was shown that for the case of clear ocean waters and considering OOK modulation and the MicroSB-30020 SiPM model, for operation depths (with respect to the Rx) larger than ∼ 250 m the link performance is not practically affected by the background noise [39].…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…Although we neglected the effect of background noise, it can severely affect the Rx performance due to the high sensitivity of SiPMs. In a recent study [39], the impact of solar background noise on the link performance was investigated for a worst-case scenario, i.e., sun at the zenith and the Rx plan directed towards the sea surface, this way, capturing the maximum solar irradiation [30]. It was shown that for the case of clear ocean waters and considering OOK modulation and the MicroSB-30020 SiPM model, for operation depths (with respect to the Rx) larger than ∼ 250 m the link performance is not practically affected by the background noise [39].…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…The received photon rate which gives the highest detected photon rate is λ max = 1/τ d and the corresponding detected photon rate is λ D,max = 1/eτ d . The non-linear distortion shown in the photon transfer function (14) would significantly influence the performance of the SPAD-based receivers [35]. To involve the non-linear distortion into the system analysis, it is commonly assumed that the detected photon count of SPAD array is Poisson distributed with effective photon rate given in (14) which is an accurate approximation in low photon arrival rate regimes as illustrated in [15], [36].…”
Section: B Performance Of the Spad Arraymentioning
confidence: 99%
“…In order to push the data rate beyond the limited BW of the opto-electronic components, two common approaches are serial transmission with channel equalization at the Rx, and the use of high spectral efficiency modulation techniques such as multiple sub-carrier modulation [8]. For instance, the use of on-off keying (OOK), pulse-amplitude modulation (PAM), and pulse-position modulation (PPM) with frequency-domain equalization (FDE) was considered in [9,10]. Several works also have considered the use of O-OFDM for UWOC links, with the advantages of using a simple single-tap equalizer to equalize the frequency-selective aggregate channel.…”
Section: High Spectral Efficiency State-of-the-art Techniquesmentioning
confidence: 99%
“…The thermal noise effect is reasonably neglected, compared to the SiPM shot noise [50]. The background noise effect is also neglected, assuming that the Rx operates in relatively deep waters [10,51]. Hence, only the shot and dark noises of the SiPM are taken into account.…”
Section: Parameter Specificationmentioning
confidence: 99%
See 1 more Smart Citation